1999
DOI: 10.1177/030089169908500407
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism and Concurrent Thyroid Cancer

Abstract: Our data confirm previous reports on the frequency of thyroid cancer in hyperthyroidism. This association is more relevant than previously suspected. The frequent coexistence of hyperthyroidism and neoplasia, demonstrated by our study and the most recent literature, underlines the importance of studying and excluding the possibility of neoplastic degeneration by means of a systematic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…In our series the incidence of hyperthyroidism in TC patients is 2.8% and the incidence of TC in active nodules is 1.2%. The data in the literature mostly report cases of TC associated with hyperthyroidism in patients with Graves' disease and these patients were reported to have more frequent TC incidence than patients with hyperfunctioning autonomous thyroid nodules [16]. None of our patients had Graves' disease and so the incidence of ToxTC in our series is quite high.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our series the incidence of hyperthyroidism in TC patients is 2.8% and the incidence of TC in active nodules is 1.2%. The data in the literature mostly report cases of TC associated with hyperthyroidism in patients with Graves' disease and these patients were reported to have more frequent TC incidence than patients with hyperfunctioning autonomous thyroid nodules [16]. None of our patients had Graves' disease and so the incidence of ToxTC in our series is quite high.…”
Section: Discussionmentioning
confidence: 59%
“…Als et al [13] reported 19 ToxTC patients in a series of 845 DTC patients found follicular carcinoma more frequent (15/19). Gabriele et al and Vaiana et al [15,16] reported papillary carcinoma more frequent in their series of ToxTC. In our ToxTC patients papillary carcinoma was predominant as was in studies of Vaiana et al and Gabriele et al…”
Section: Discussionmentioning
confidence: 87%
“…We concluded that patients' age at the time of diagnosis couldn't predict the final outcome, but the mean age in our study was less than in previous studies (39.3 ± 13.0 years). It could be a consequence of an earlier diagnosis, probably due to our particularly attention to thyrotoxicosis as previously demonstrated [37,38].…”
Section: Discussionmentioning
confidence: 80%
“…Incidence in thyrotoxicosis has been reported at different rates from different countries or different centers from the same country [1,2,3,4,5,6] (table 2). This difference may be elucidated with patient populations from different geographical areas and iodine intake, exposure to ionizing radiation, the type of surgery, changing selection criteria for surgery and definition of pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid carcinoma causing thyrotoxicosis or arising from hyperfunctioning nodules, which is reported to be quite rare, and thyroid carcinoma detected incidentally in patients who are operated for thyrotoxicosis. The incidence for the latter condition has been reported at different rates changing between 0.21 and 16.6% by several authors [1,2,3,4,5,6]. Treatment of choice for thyrotoxicosis in some countries is radioactive iodine (RAI) for both cost-effectiveness and concerns about morbidity and mortality related to surgery.…”
Section: Introductionmentioning
confidence: 99%